2008
DOI: 10.1039/b805589k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cross-linked adducts between guanine and thymine mediated by hydroxyl radical and one-electron oxidation: a theoretical study

Abstract: The role of local geometric and stereo-electronic effects in tuning the preference for different cross-linked adducts between thymine and purinic bases has been analyzed by a computational approach rooted in density functional theory. Our study points out that G--T and T--G tandem lesions are produced according to the same mechanism as A--T and T--A intrastrand adducts, and in both cases purine--T adducts are preferred rather than the opposite sequences. Moreover, use of conceptual DFT tools allows the rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 19 publications
2
60
0
Order By: Relevance
“…32 Interestingly, the possible formation of such tandem lesions was also studied in silico, 33 confirming the possible formation of endoperoxide 4 and providing a possible explanation for the sequence preference observed experimentally. 32 Similar theoretical approaches have been used 34,35 to study the formation of other tandem lesions that are generated in the absence of oxygen. Under these conditions, intrastrand crosslinks can be produced between a pyrimidine and a purine base 7 as initially reported by Box et al, 36,37 and a similar sequence effect has been observed.…”
Section: Complex Dna Lesions Induced By a Single Oxidation Eventmentioning
confidence: 99%
“…32 Interestingly, the possible formation of such tandem lesions was also studied in silico, 33 confirming the possible formation of endoperoxide 4 and providing a possible explanation for the sequence preference observed experimentally. 32 Similar theoretical approaches have been used 34,35 to study the formation of other tandem lesions that are generated in the absence of oxygen. Under these conditions, intrastrand crosslinks can be produced between a pyrimidine and a purine base 7 as initially reported by Box et al, 36,37 and a similar sequence effect has been observed.…”
Section: Complex Dna Lesions Induced By a Single Oxidation Eventmentioning
confidence: 99%
“…In that framework, Prof. Barone and collaborators have demonstrated that theoretical chemistry provides a useful and deep understanding of the interactions between UV-visible radiation and DNA. Their studies unravel the nature of the excited state of nucleic acids [1][2][3][4][5] and the subsequent implications for life that they rationalize as radiation-induced changes in DNA canonical structure [6][7][8]. Interestingly, not only external factors might tune the biological functions of DNA but natural components such as metallic cations (mainly Na ?…”
Section: Introductionmentioning
confidence: 97%
“…In addition, efforts were made to delineate the reactivity of defined base or sugar radicals upon their mild generation usually by UV activation of a photolabile precursor at a specific site within a defined sequence DNA fragment [20,21]. Theoretical calculation approaches gradually emerged through the development of highly performant ab initio DFT based computational and simulation methods, all of which have provided relevant information about the reactivity and energy requirements of key intermediates, which is not accessible experimentally [2225]. Based on detailed structural and mechanistic studies, one may propose comprehensive oxidative degradation pathways of the main nucleic acid components upon exposure to 1 O 2 , • OH, one-electron oxidants, halogenating agents and cellular dioxygenases; this information has been recently critically reviewed in exhaustive surveys.…”
Section: Introductionmentioning
confidence: 99%